Edukacja stylistyczna a stan współczesnej metodologii = Stylistic education versus the state of contemporary methodology - Bogołębska, Barbara (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The article is an at temp of defining the aim, the place, the scope and the meaning of stylistic problems in contemporary didactic and indicates the substantial and methodogical relations between didactic theory and the doctrines of linguistic and literary theories. Nowadays the instrumental and functional models of teaching stylistic are preferred and practical stylistic gains in meaning. Stylistic is the thematic part of linguistic, literary and cultural education. Different kinds af stylistic are cansidered in school: theoretical and practical, linguistic and literary, synchronical and diachronical as well as general and particular (functional). Stylistic plays a great role in exploration of literary work in school. The article ends with painting the six of peculiar autonomos rules of teaching stylistic.
Keywords: dydaktyka literatury; metodologia